Fatty acid‐based diet estimates suggest ringed seal remain the main prey of southern Beaufort Sea polar bears despite recent use of onshore food resources. Issue 4 (29th January 2020) - Bourque, Jennifer; Atwood, Todd C.; Divoky, George J.; Stewart, Connie; McKinney, Melissa A.
Abstract: Polar bears ( Ursus maritimus ) from the southern Beaufort Sea (SB) subpopulation have traditionally fed predominantly upon ice‐seals; however, as the proportion of the subpopulation using onshore habitat has recently increased, foraging on land‐based resources, including remains of subsistence‐harvested bowhead whales ( Balaena mysticetus ) and colonial nesting seabirds has been observed. Adipose tissue samples were collected from this subpopulation during the springs of 2013–2016 and analyzed for fatty acid signatures. Diet estimates were generated for the proportional consumption of ringed seal ( Pusa hispida ), bearded seal ( Erignathus barbatus ), and beluga whale ( Delphinapterus leucas ), relative to onshore foods, including bowhead whale remains and seabird, as represented by black guillemot ( Cepphus grylle mandtii ) nestlings and eggs. Quantitative fatty acid signature analysis (QFASA) estimated that the ice‐obligate prey, ringed seal, remained the predominant prey species of SB polar bears (46.4 ± 1.8%), with much lower consumption of bearded seal (19.6 ± 2.0%), seabird (17.0 ± 1.2%), bowhead whale (15.0 ± 1.4%), and hardly any beluga whale (2.0 ± 0.5%). Adult and subadult females appeared to depend more on the traditional ringed seal prey than adult and subadult males. Diet estimates of SB polar bears showed significant interannual variability for all prey ( F 12, 456 = 3.17, p < .001). Longer‐term estimates suggested that both types of onshore prey, bowhead whale remains and seabird, have represented a moderate proportion of the food resources used by SB polar bears since at least the start of the 21st Century. Abstract : Polar bears in the southern Beaufort Sea are increasingly using land‐based habitat. This work suggests that these polar bears still rely heavily on ringed seal, although onshore seabirds and whale carcasses have represented a moderate proportion of their diet since at least the turn of the 21st century.